KAJIAN ANTROPOLOGI SASTRA: CERITA RAKYAT LAKIPADADA DAN PENGARUHNYA DALAM KEHIDUPAN MASYARAKAT [An Antropology Study on Literature: The Folklore of Lakipadada and Its Influence in Social Life] - Mustafa - (TOTOBUANG, 2020)
Lakipadada is one of the    Toraja Literary which is filled with the values and concepts of life. it has delivered orally from generation to generation. This paper describes one type of local literary works that felt under legend category. The story told about a noble young man who has death paranoid, therefore he tried to find ‘tang mate’ ‘ternal’ so not being haunted by death.  To make this  story become more interesting to read and digest, the author  put a lot of superstitious contents. Moreover, the story can be an advicing and learning source  for the next generations so they will live in the right path of life. . The basic problem that arise in this article is about common belief on how Toraja people (Lakipadada ) will never be crowned as king beyond its own community (Toraja), and also will hard to socialize with other community than Toraja people.. Does this common assumption have any correlations with the content of the story?. The theory that used in this story was structurilism based on Levi-Staruss as exemplified by Ahimsa in the book Structurilism of Levi-Staruss, A myth and Literary Works (2001: 216-256) and it also used descriptive analysis method. The results indicated a structured relationship among elements in the story and social conditions in society.Lakipadada adalah salah satu karya sastra daerah masyarakat Toraja yang sarat dengan nilai-nilai dan konsep-konsep kehidupan. Karya sastra ini disampaikan secara lisan dan turun temurun. Tulisan ini bertujuan mendeskripsikan salah  satu karya sastra daerah yang masuk  kategori legenda. Cerita ini berkisah tentang seorang pemuda bangsawan yang paranoid akan kematian sehingga dia berusaha mencari mustika tang mate ‘kekal abadi’ agar tidak lagi dihantui kematian. Kisah ini   banyak dibumbui cerita supranatural sehingga  menarik untuk dibaca dan dipahami. Disamping itu, kisah ini dapat menjadi bahan nasihat dan pembelajaran bagi anak cucu untuk bekal di hari mendatang agar tidak salah langkah/tersesat. Masalah  mendasar  yang  muncul  dalam  artikel  ini  adalah  adanya asumsi bahwa manusia Toraja (Lakipadada ) tidak bisa menjadi raja di luar daerah Toraja  dan  tidak bisa membaur dengan masyarakat di luar orang Toraja. Apakah anggapan masyarakat ini mempunyai relasi dengan muatan cerita? . Teori yang digunakan adalah teori strukturalisme berdasarkan Levi-Staruss  seperti yang dicontohkan Ahimsa dalm bukunya Strukturalisme Levi-Strauss Mitos dan Karya Sastra (2001: 216-256) dengan metode analisis deskriptif. Hasil yang ditemukan menunjukkan adanya hubungan yang terstruktur antarelemen dalam cerita dan kondisi sosial di masyarakat.